Medical economic efficiency of various schemes of rehabilitation of children with chronic gastroduodenitis - A. M. Shakhova; Yu. F. Lobanov (Бюллетень сибирской медицины)
Medical economic efficiency of various schemes of rehabilitation of 120 children with chronic gastroduodenitis is studied. The Most economic scheme of rehabilitation of children with chronic gastroduodenitis is the scheme with use of training of children in gastroschool. Sanatorium treatment considerably raises mediko-economic efficiency of rehabilitation actions.